1985
DOI: 10.1037/0003-066x.40.3.355
|View full text |Cite
|
Sign up to set email alerts
|

The validity of polygraph testing: Scientific analysis and public controversy.

Abstract: Polygraph tests to detect deceptiveness have been conducted for many years, although their validity has not yet been established. The present review was conducted to aid Congressional consideration of efforts by the Department of Defense and President Reagan to expand use of polygraph tests to large numbers of government employees with access to classified information. Results of this review suggest serious problems with both the theoretical rationale underlying use of polygraph tests and the quality of availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 55 publications
2
71
0
1
Order By: Relevance
“…It is unknown whether the type of polygraph test administered impacts upon the validity of the outcomes; however, some researchers have suggested that the method of questioning employed may have an influence on the outcomes (Saxe et al, 1985). The type of polygraph test employed was not specified in four of the included studies (Kokish et al;Ahlmeyer et al, 2000;Grubin et al, 2014;Grubin & Madsen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether the type of polygraph test administered impacts upon the validity of the outcomes; however, some researchers have suggested that the method of questioning employed may have an influence on the outcomes (Saxe et al, 1985). The type of polygraph test employed was not specified in four of the included studies (Kokish et al;Ahlmeyer et al, 2000;Grubin et al, 2014;Grubin & Madsen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many integrity tests were developed for use where polygraphs were not permitted (Sackett, Burris, and Callahan, 1989). As more research questioned the use and effectiveness of polygraphs (e.g., Saxe, Dougherty, and Cross, 1985), Congress passed the Employee Polygraph Protection Act of 1988, prohibiting many U.S. employers from requiring or requesting that applicants or employees complete polygraphs but allowing exceptions for federal-, state-, and localgovernment employers. While the Air Force is permitted to use polygraphs, administering them to all Air Force accessions would be prohibitively costly.…”
Section: Integrity Testsmentioning
confidence: 99%
“…Although the extensive debate on the accuracy of the polygraph is outside the scope of this report (see Office of Technology Assessment, 1983;Saxe, Dougherty, & Cross, 1985;lacono & Patrick, 1987;Lykken, 1981;and Sackett & Decker, 1979 for excellent reviews), two aspects of the polygraph method--the pre-examination method and the questioning technique--are relevant to the investigative interview.…”
Section: Physioloqical Measuresmentioning
confidence: 99%